Non-Steroidal Anti-inflammatory Drugs (NSAIDs): Synthesis of Ibuprofen, Naproxen and Nabumetone - Ayad M. R Raauf; Sura S. Raauf; Nehad Kanaan Abed; Hala Ayad M (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
This review paper covers the major synthetic approaches attempted towards the synthesis of some Non-Steroidal Anti-Inflammatory Drugs (Naproxen, Ibuprofen and Nabumetone)